Analisis Sistem Just In Time Meningkatkan Produktivitas (Studi Kasus Usaha Batu Tela Beton Mas) - Irsyad Hardinansah; Dirarini Sudarwadi; Nurwidianto (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2020)
This study aims to determine the application of the Just In Time system at the Batu Tela Beton Mas Business in an effort to increase company productivity. This study uses primary data and secondary data with data collection techniques using interviews, observation and documentation. The results of the study show that using the Just In Time system on the purchasing system and production system can increase the productivity of the company. This is proven to be true that the implementation of the Just In Time purchasing system can reduce storage costs. Implementation of the Just In Time Purchasing system can directly have a large impact on cost efficiency and productivity. The application of the Just In Time Production system is able to suppress activities that do not add value (non value added) or improve manufacturing cycle efficiency. The increase in MCE is caused by the smaller activities that do not add value (non value added) to the production process. With increasing MCE due to loss of activity that does not add value. then the application of the Just In Time Production system can increase company productivity. The implication of the results of this study is to give advice to companies so that companies should implement the Just In Time system in managing the company so that it can increase the productivity of the company.